Awareness of Social Influences on Eating Is Dependent on Familiarity With Imagined Dining Partners and Type of Eating Occasion - Higgs, Suzanne; Bouguettaya, Ayoub; Ruddock, Helen (Frontiers in Psychology, 2022)
When eating with strangers, people tend to eat less than they would when eating alone (social inhibition of eating), whereas they tend to eat more with family and friends (social facilitation of eating). To assess awareness of the social inhibition and facilitation of eating we conducted two online studies (Study 1:N=481; Study 2:N=485). In Study 1, participants imagined a dining scenario and indicated whether they would eat the same, more, or less when eating with someone who was more or less familiar to them (friend; family member; acquaintance; stranger) compared with when eating alone. Results from Study 1 indicated that participants imagined eating special meals with friends/family and so, in Study 2, another group of participants made the same predictions as for Study 1, but they did so for special and regular meals. In Study 1, a significant majority of participants said that they would ‘eat less’ with a stranger/acquaintance. A similar proportion of participants said that they would ‘eat the same’ or ‘eat more’ when with a friend/family member and significantly fewer participants said that they would ‘eat less’ with a friend/family member. In Study 2, the majority of participants said that they would ‘eat less’ with a stranger across both special and regular meals. For meals with an acquaintance, the majority of participants reported that they would ‘eat the same’ during regular meals, while for special meals, equal numbers said that they would ‘eat the same’ as would ‘eat less’. The majority of participants indicated that they would ‘eat more’ during a special meal with a friend/family member. However, for regular meals with a friend/family member, a significant majority of participants said that they would ‘eat the same’. Hence, participants acknowledge the social inhibition of intake and the social facilitation of eating at special meals, but they are either unwilling or unable to acknowledge that they would eat more with a friend/family member at a regular meal compared with eating alone. Raising awareness that eating with friends/family is associated with greater intake at regular meals may be helpful for individuals who are trying to manage their intake.